A survey of phytoestrogenic activity in Kansas flint hills pastures - Paisley, S.I.; Welshons, W.V.; Rottinghaus, G.E.; Davidson, Jeffrey L.; Higgins, James J.; Blasi, Dale A.; Holder, Michael S.; Kehler, David E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
The botanical composition and basal cover of three Kansas Flint Hills pastures located in Butler and Chase counties was surveyed to estimate the incidence of plant species that contain appreciable levels of estrogenic activity. Many-flowered scurfpea and Ladino clover were the only plant species classified as high in estrogenic activity. Although significant estrogenic activity existed in specific species, the willingness of livestock to consume those species is unclear.
Keywords: Beef; Flint Hills pastures; Phytoestrogen; Buller steer syndrome